SOCIAL DEVELOPMENT IN SOUTHERN AFRICA IN THE WAKE OF COVID-19 - Mpumelelo Ncube (Social Work/Maatskaplike Werk, 2024)
Modern capitalism has shaped the world, but for many scholars, its principles have disproportionately favoured the prosperity of a minority while neglecting the prospects of the majority, particularly in Southern Africa. The recent COVID-19 pandemic combined with significant inequalities of wealth has put the social policies of countries in Southern Africa to the test. It exposed the inadequacies of the current capitalist order in many countries in the global south, hindering their ability to protect their populations from the pandemic’s impact. In contrast, the global north, with stronger social policies and economic flexibility, managed to cushion the severity of pandemic’s economic impact on their populations in many ways, even though they suffered the most deaths. In this article, I establish how COVID-19 and neoliberal capitalism made it difficult to achieve the social developmental objectives in Southern Africa. While scholars have documented the medical and economic harms caused by the pandemic, I highlight ways that it, along with considerable inequalities of wealth, impaired social development more broadly. I conclude by establishing how the COVID-19 pandemic has underscored the shortcomings of neoliberal capitalism in Southern Africa’s social policies, emphasising the need for re-evaluating and re-alignment of these policies to foster more equitable and resilient societies.